Public Service Performance of the Tuban Regency Fire and Rescue Service - Sutaji Sutaji; Fedianty Augustinah; Ika Devy Pramudiana (Perspektif Administrasi Publik dan hukum, 2025)
This study aims to describe and analyze: Public service performance and what are the inhibiting factors that affect the performance of public services at the Tuban Regency Fire and Rescue Service. The type of research used is qualitative research. The data analysis technique in the study uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that the Public Service Performance of the Tuban Regency Fire and Rescue Service is quite good, this is based on the Realization of the Indicator of Achieving Minimum Service Standards for Basic Service Types in 2023, Rescue and Evacuation Services for Fire Victims reached 96.89%. Based on the elements of the service procedure The performance is good, the media used for the service procedure is clear, displaying a picture of the flow of complaint procedures. Based on the element of service time including completion time, the requirements are good. The completion time for settlements, industrial areas, and public buildings is a maximum of 15 minutes, and for certain forest and fire areas is a maximum of 60 minutes. Based on the element of Service Transparency is good, there is a bulletin board that provides information about services, requirements, costs, completion times and management mechanisms. Based on the Ease of Service element is good, the location of the Tuban Regency Fire Service counter is easily accessible and strategically located, the service procedure is easy to understand. Based on the element of justice The service is good, providing services to people who need help is not picky, anyone who reports and asks for help will be assisted according to their ability. Based on the element of competence of service officers, officers are equipped with Standard Operating Procedures (SOP). Inhibiting factors include: Lack of public understanding of fire hazards and people's readiness to face and overcome fires is very low. Lack of Facilities and Infrastructure, only has 3 auxiliary posts. The Tuban Regency Fire Department has 6 fire engines, and does not yet have a Power Supply Vehicle. Limited Human Resources where in each sub-district post there are 16 personnel on standby and 1 fire truck, only 15 personnel have participated in a number of trainings. But only 4 of them have certification